A Bibliometric Analysis of Instructional Technological Leadership Research Using VOSviewer - Fauziah, R. Siti Pupu; Suherman, Irman; Kholik, Abdul; Ramdhani, Muhammad Rendi; Lathifah, Zahra Khusnul (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This study aims to analyze the development of research on technology-related instructional leadership. The research method used is bibliometric analysis. The articles used in this study were sourced from the Google Schooler database with the help of the Publication of Perish from 2015-2022; 498 papers were found. Data analysis using the VOSviewer application. The results showed that the number of publications decreased yearly, where the most occurred in 2015, namely 102 publications. The results of the density visualization analysis shown in yellow circles indicate the themes most frequently used in recent research, namely instructional technology, technology integration, instructional leadership practice, school leader, transformational leadership, covid, time and student. Meanwhile, based on network visualization, the topic of instructional leadership has a relationship with the term development, effect, effectiveness, instructional leader, instructional leadership, instructional leadership practice, leader, leadership, model, principal, research, school, school leader, school leadership, school principal and transformational leadership. These results illustrate that technology-based instructional leadership can be developed by referring to instructional technology, technology integration, as a term rarely used based on visualization overlay.